Effect of Storage Conditions and Disinfection with 2% Deconex® on Dimensional Stability of Two Self-Cure Acrylic Resins - Shima Safaeian; Sareh Habibzadeh; Seyed Jalal Porhashemi; Niloofar Entezari Moghaddam (Islamic Dental Association of Iran, 2018)
Background and Aim: There is a gap of information on the effect of time, disinfectant, and storage conditions on the dimensional stability of direct post patterns made of self-cure acrylic resins. This study assessed the effect of Deconex® and wet or dry stor-age conditions on the dimensional stability of post patterns made of Duralay and GC acrylic resins. Materials and Methods: Sixty specimens were fabricated of GC and Duralay acrylic resins (n=30) by using a stainless steel mold. The specimens in each group were divided into three subgroups (n=10). The specimens of subgroup 1 were immersed in Deconex® for 2 minutes followed by dry storage at 25°C. The specimens of subgroup 2 were stored in water at 25°C. The samples of subgroup 3 were immersed in Deconex® for 2 minutes followed by water storage at 25°C. The dimensions were measured immediately and 2 minutes, 1 hour, and 24 hours after setting. Data were analyzed by repeated measures ANOVA. One-way ANOVA and t-test were used for subgroup analysis at 5% significance level. Results: The greatest mean dimensional changes occurred after 24 hours in both groups. In GC group, subgroup 1 experienced minimal changes during 24 hours. Duralay subgroups 1 and 2 experienced minimal changes after 1 and 24 hours; the difference between the two subgroups was not significant. Maximum changes were noted in GC subgroups 2 and 3 and in Duralay subgroup 3 (P<0.05). Conclusion: In case of a 24-hour delay, storage conditions would have no effect on the dimensional stability of Duralay patterns, while GC patterns should be stored in a dry condition.